DETERMINANTS OF COMMUNITY WELFARE IN NON-SARBAGITA REGIONS IN BALI PROVINCE - Ni Putu Eka Putri Adnyani; Putu Ayu Pramitha Purwanti (Adisam Publisher, 2025)
Community welfare refers to the fulfillment of citizens’ needs across economic, educational, and health dimensions, enabling individuals to live decently and develop their potential. In this study, community welfare is measured using the Human Development Index (HDI). This study aims to analyze the influence of GRDP per capita, minimum wage, population size, and average years of schooling on the welfare of communities in non-Sarbagita regions in Bali Province. The study employs secondary data, comprising 50 observations. The analytical methods used include descriptive statistics and panel data regression analysis. The findings reveal that (1) GRDP per capita, minimum wage, population size, and average years of schooling simultaneously have a significant effect on community welfare in the non-Sarbagita regions of Bali Province; and (2) each of these variables also has a positive and significant partial effect on community welfare in these areas.